Penerapan dan Penyimpangan Maksim Kerja Sama Grice dalam Podcast Sule Bersama Rizwan Media Sosial Youtube: Analisis Pragmatik - Dinar Thahira Handatika; Farida Yufarlina Rosita; Berlian Pancarrani (BLAZE : Jurnal Bahasa dan Sastra dalam Pendidikan Linguistik dan Pengembangan, 2025)
This study aims to examine the application and deviation of conversational maxims in Grice's cooperative theory in the podcast "Sule and Rizwan". This podcast was chosen because it presents interactions full of humor, spontaneity, and communication dynamics that are interesting to study pragmatically. The research method used is descriptive qualitative with listening and note-taking techniques as data collection instruments. Data in the form of utterances containing maxims of quantity, quality, relevance, and method are analyzed based on Grice's cooperative principle. The results of the study show that the speakers in this podcast consciously or unconsciously apply the four Grice maxims, but also often deviate from them for the purpose of humor, satire, or dramatic effect. These deviations do not interfere with communication, but rather enrich the meaning and strengthen the appeal of the conversation. These findings indicate that violation of maxims in the context of entertainment is not a form of communication failure, but rather an effective pragmatic strategy.